Design and implementation of pipelined and parallel AES encryption systems using FPGA - Mohamed Nabil; Ashraf A. M. Khalaf; Sara M. Hassan (Institute of Advanced Engineering and Science, 2020)
The information security is one of the most important issues in the design of any communication network.One of the most common encryption algorithms is the advanced encryption standard (AES).The main problem facing the AES algorithm is the high time consumption due to the large number of rounds used for performing the encryption operation. The more time the encryption system consumes to encrypt the data, the more chances the hackers have to break the system.This paper presents two effective algorithms that can be used to solve the mentioned problem and to achieve an effective processing time reduction using pipelined and parallel techniques to perform the encryption steps. These algorithms are based on using certain techniques to make the system able to encrypt many different states (the data will be encrypted) in the same time with no necessity to wait for the previous encryption operation to be completed. These two algorithms are very effective especially for big data size. This paper describes in detail the AES encryption system algorithm and a detailed explanation for the proposed algorithms. Moreover, the research shows the implementation of the three algorithms: the traditional, the pipelined, and the parallel algorithms, and finally a comparison between them.